The Expanding Complexity of Estrogen Receptor Signaling in the Cardiovascular System. Issue 6 (18th March 2016) - Menazza, Sara; Murphy, Elizabeth
Abstract : Estrogen has important effects on cardiovascular function including regulation of vascular function, blood pressure, endothelial relaxation, and the development of hypertrophy and cardioprotection. However, the mechanisms by which estrogen mediates these effects are still poorly understood. As detailed in this review, estrogen can regulate transcription by binding to 2 nuclear receptors, ERα and ERβ, which differentially regulate gene transcription. ERα and ERβ regulation of gene transcription is further modulated by tissue-specific coactivators and corepressors. Estrogen can bind to ERα and ERβ localized at the plasma membrane as well as G-protein–coupled estrogen receptor to initiate membrane delimited signaling, which enhances kinase signaling pathways that can have acute and long-term effects. The kinase signaling pathways can also mediate transcriptional changes and can synergize with the ER to regulate cell function. This review will summarize the beneficial effects of estrogen in protecting the cardiovascular system through ER-dependent mechanisms with an emphasis on the role of the recently described ER membrane signaling mechanisms.